A six-coordinate high-spin FeIVO species of cucurbit[5]uril: a highly potent catalyst for C–H hydroxylation of methane, if synthesised. Issue 100 (2nd December 2021) - Kumar, Ravi; Sundararajan, Mahesh; Rajaraman, Gopalan
Abstract : In silico design predicts an S = 2 high-spin Fe IV O species with a cucurbit[5]uril ligand with unprecedented reactivity. Abstract : DFT and ab initio DLPNO-CCSD(T) calculations predict a stable S = 2 six-coordinate Fe IV O species with cucurbit[5]uril (CB[5]) as a ligand ([(CB[5])Fe IV O(H2 O)] 2+ (1 )). The strong oxidising capability of 1 far exceeds even that of metalloenzymes such as sMMOs in activating inert substrates such as methane, setting the stage for a new generation of biomimetic catalysts.